Problems of Online Learning according to Students during the Covid-19 Pandemic - Umar Mansyur; Ihramsari Akidah; Rizkariani Sulaiman (STAI Hubbulwathan Duri, 2022)
This study aims at describing the types of problems experienced by students while participating in online learning, online learning media that students prefer, and evaluation of the implementation of online learning according to students at the Indonesian Muslim University during the Covid-19 pandemic. This study uses a survey method. The research sample is the students of the Faculty of Letters. The data collection technique used in this study is Google form questionnaire and analyzed by using quantitative descriptive statistics. The results show that the types of problems experienced by students while participating in online learning are generally caused by two factors, namely internal factors: unable to focus on attending lectures, problem on internet network, lack of cost to buy internet quota, and external factors: class schedules change frequently, the use of less effective learning media, redundant assignments. Online learning media that are generally preferred by students are Zoom Meeting, UMI Kalam e-Learning, and WhatsApp. According to students, some points that need to be evaluated in online learning include: lecturers often change class schedules and immediately organize face-to-face learning, lecturer learning strategies are less effective, giving excessive assignments, internet connections often in problems, students need to receive internet quota fund, and lecturers are still less skill in using digital learning media.